Causal Effect Relationship in Medical Cases. An Old Problem in a New Scenario. Commentary to CJEU Judgment (Second Chamber) of 21 June 2017, N.W. & Others V. Sanofi Pasteur MSD & Others, Case C-621/15, EU:C:2017:484. Approbative Gloss - Wnukiewicz-Kozłowska, Agata; Drozdowska, Urszula Dorota (Review of European and Comparative Law, 2021)
This commentary evaluates the problem in assessing the role of a causal connection between damage and the use of a defective medical product, specifically a vaccine. The judgment of the Court of Justice of the European Union (CJEU) in the Sanofi Pasteur Case, which allowed the possibility of recognizing damage claims, even in cases where the prevailing scientific theory claims that there is no scientific evidence of a causal link between a vaccination and the disease, became a base for consideration. Consequently, procedural solutions (such as the standard of proof required, the admissibility of prima facie evidence reasoning and other solutions in cases of an uncertain causation) remain to be decided by national law. The authors assessed two legal systems: the French and Polish legal systems in the context of how to resolve these dilemmas and to describe the impact of the above-mentioned judgment on the case-law of French and Polish courts as regards the application of Directive 85/374/EEC. As a result, they concluded that the most important interpretative motive has become the individual interest of the vaccination’s victim as a consumer of medical services. It seems to be in accordance with Directive 85/374/EEC, which is motivated by the necessity of approximation of the laws of the Member States concerning the liability of the producer for damage caused by the defectiveness of his products. However, since the existing divergences may distort competition and affect the movement of goods within the common market and entail a differing degree of protection of the consumer against damage caused by a defective product to his health or property, in countries belonging to the European Union, the authors wonder how the commented judgment will affect the further development of consumers protection against defective vaccines.